Designing to Speech Therapy of Augmented Reality Technology: Needs Identification - Manik Mahachandra; Abel Kristanto Widodo; Wiwik Budiawan (Center for Biomechanics, Biomaterials, Biomechantronics and Biosignal Processing (CBOIM3S), 2022)
Speech Delay (primary) is one of the high contributors to the case of children's speech delay. That matter occurs due to the lack of child interaction in this modern era. The speech delay treatment can be provided in flashcards, hand puppet stories, multimedia, mobile applications, and computer games. The handling has not fulfilled the multisensory (visual, auditory, and tactile) components children need. Augmented reality technology will be the answer as a tool for speech therapy because children will interact significantly with virtual objects that have been combined with conditions in the real world. Before using augmented reality, it is necessary to identify the appropriate needs. The process of identification by the Delphi method for the design factors for speech therapy aids with Ulrich & Eppingger until the concept development stage. Delphi results indicate three main factors, i.e., visual, sound, and interactive technology, which become the basis of planning. The design will generate a low-fidelity prototype. Usability test results obtained: Effectiveness (82%), Efficiency (0.01285 goals/sec), and Satisfaction (87%) with task performance easy to do. Speech therapy aids are recommended at the cost of 100,000 IDR. The companion is willing to use this speech therapy aid if it is recommended or the product is sold.